Crossing the border; Historical and linguistic divides among the Bunaq in central Timor - Schapper, Antoinette (UI Scholars Hub, 2011)
The Bunaq are a Papuan language-speaking people straddling the border of Indonesian West Timor and independent East Timor. This paper looks at the history of the Bunaq as a